Bangunan Pintar dan Penerapannya di Indonesia - Hannisa Handri; Zulfikar Taqiuddin; Khairul Huda (Universitas Syiah Kuala, 2021)
Smart building is a building concept that can provide automated technology to meet service convenience and building efficiency. This concept was born as a result of human welfare and changes in modern lifestyles that demand a high level of service and management of the building environment. Smart building systems have goals that can reduce operating costs, ensure the use of buildings, and prevent the frequent replacement of building equipment. The benefits provided if this concept is applied are also many for both building owners and users. The requirements for implementing this concept are to have the latest automation system, have a good network infrastructure, and provide adequate telecommunications facilities. Currently, Indonesia is in the process of implementing this concept, Indonesia's opportunities are quite large but there are also several challenges that Indonesia must face such as the lack of human resource capabilities (HR), lack of development technology, and high investment costs. Several commercial and public buildings in Indonesia are trying to implement the smart building concept, one of which is the Senayan City Shopping Center in Jakarta. Although the implementation is not optimal, it can still be developed.